Native brazilian population in Amazon region: a methodology for research-action in environmental education - Ferraz de Toledo, Renata; Focesi Pelicioni, Maria Cecília; Giatti, Leandro Luiz; Pranzetti Barreira, Luciana; Audrá Cutolo, Silvana; Viero Mutti, Luciane; Almeida Rocha, Aristides; Rios, Leonardo (O Mundo da Saúde, 2006)
This study aims to describe the environmental education process developed on a native community in order to identify health-disease representations and to improve life conditions of local people exposed to socio-environmental impacts and to health risks due to the increasing population associated to the lack of sanitation and the persistence of traditional habits. This research used a research-action methodology in the environmental education process that was applied to community meetings using different techniques, such as questionnaires, interviews, talking-maps, photography panels and active observation The research revealed that despite the indigenous population’s awareness of the concrete situation of socio-environmental degradation and situations potentially hazardous to their health, but were as yet unable to incorporate that knowledge to their daily life. Even though the inhabitants who interacted in the research were keen to improve sanitation, it is now clear that offering infra-structural changes will not be enough to guarantee their health, nor breaking the cycle of disease transmission. It is also necessary to continue to promote education processes that bring about a critical understanding of reality and its transformations, thus reinforcing healthy habits that might contribute to an improvement in their living standards. The research-action proved to be an extremely adequate methodology for environmental education processes that intend to find solutions to problems by means of participation and dialogue, as well as improving the general living standard.